ANALISIS KINERJA RUAS JALAN MENGGUNAKAN METODE MANUAL KAPASITAS JALAN INDONESIA (MKJI) 1997 PADA RUAS JALAN JEPARA-KUDUS KM 11 SAMPAI KM 15 - Suryo Angkoso, Guntur (Jurnal Civil Engineering Study, 2021)
The city of Jepara is one of the areas that is undergoing rapid development, where the population is insecreasing over time. Jepara is the center of all economic activity, the impact of traffic in the city of Jepara is very heavy, so that traffic jams often occur on certain roads. This happens because the number of vehicles that pass through the route is not balanced with the capacity of the road and the high activity of side barriers. In this thesis, the author raises the topic of Road Performance Analysis of the Jepara – Kudus road segment. The method applied in analyzing the road used the Manual Kapasitas Jalan Indonesia (MKJI) 1997. The study was conducted for 7 days, Monday to Sunday on the Jl. Jepara – Kudus. After doing research on the road section, it can be concluded that the road has the highest average speed of 38.19 km/hour on Sunday and the capacity of the road with side barriers (road body parking) is 2220,24 smp/hour, while the degree is 2220,24 smp/jam. The road saturation (DS) is > 0,75 which is 1.526 which is included in the service leecel category F with the number of vehicles being 3390.25 smp/hour/2 directions. So it is necessary to widen the road on the Jepara – Kudus road section Km 11 – Km 15.